Effectiveness of fluorescent pseudomonads in the management of sclerotial wilt of cotton - and R.P. SINGH, G.S. LAHA*, J.P. VERMA (Indian Phytopathology, 2002)
Of 48 fluorescent pseudomonad isolates from cotton seedling rhizospheres, 16 were antagonistic to Sclerotium rolfsii [Corticium rolfsii], the causal agent of cotton wilt. C. rolfsii growth was suppressed in vitro by volatile cyanogenic metabolites produced by the isolates, though inhibition was reduced by the addition of ferric chloride to the growth medium. Sclerotial viability was reduced when immersed in a bacterial suspension or in cell-free bacterial culture filtrates. In greenhouse experiments isolate FP-47 was most effective in significantly reducing the disease when seeds were inoculated with isolate cell suspensions prior to sowing.